การใช้ประโยชน์จากทรัพยากร ความหลากหลายทางชีวภาพ และภูมิปัญญาท้องถิ่น เพื่อการท่องเที่ยวในพื้นที่คุ้งบางกะเจ้า อำเภอพระประแดง จังหวัดสมุทรปราการ - ไทรชมภู ศรีณัฐ (Academic Journal Phranakhon Rajabhat University, 2015)
การวิจัยเรื่องนี้ มีวัตถุประสงค์เพื่อ 1) ส่งเสริม การใช้ประโยชน์ ผลิตภัณฑ์จากทรัพยากรความหลาก หลายทางชีวภาพ และภูมิปัญญาท้องถิ่น 2) จัดทำสื่อ สำหรับผลิตภัณฑ์จากทรัพยากรของชุมชน ที่เป็นอัต ลักษณ์และมีความโดดเด่น เพื่อการท่องเที่ยวพื้นที่คุ้ง บางกะเจ้า โดยใช้วิธีวิจัยเชิงคุณภาพ เก็บรวบรวมข้อมูล ด้วยการศึกษาเอกสาร การสำรวจพื้นที่ การสังเกต การ สัมภาษณ์ จัดกลุ่มสนทนา และคัดเลือกผลิตภัณฑ์ ทางการท่องเที่ยวจากทรัพยากรของชุมชนร่วมกับ ผู้นำ ชุมชน ปราชญ์ท้องถิ่น หน่วยงานที่เกี่ยวข้อง จำนวน 36 คน จัดทำสาระสำคัญทั้งภาษาไทยและภาษาอังกฤษ ประกอบภาพถ่ายผลิตภัณฑ์ทางการท่องเที่ยว เป็นป้าย สื่อความหมายบอกเล่าเรื่องราว เพื่อให้นักท่องเที่ยวได้ รู้ถึงคุณค่าและเข้าใจด้วยตนเอง ผลการวิจัยพบว่า พื้นที่คุ้งบางกะเจ้ามีประวัติ วิถีวัฒนธรรม ทรัพยากร ความหลากหลายทางชีวภาพ ภูมิปัญญาท้องถิ่นที่หลากหลาย และผลิตภัณฑ์จาก ทรัพยากร ความหลากหลายทางชีวภาพ และภูมิปัญญา ท้องถิ่นที่มีอัตลักษณ์เฉพาะถิ่น มีความโดดเด่น เป็นสื่อ นำเสนอเพื่อการท่องเที่ยว ได้แก่ พิพิธภัณฑ์มอญวัดคัน ลัด หอวัฒนธรรมวัดบางกระสอบ วัดราษฎร์รังสรรค์ ภูมิปัญญาสลักหยวกกล้วย น้ำตาลมะพร้าว ศิลปะการ ตัดกระดาษ เรือนเพาะชำไม้ประดับใบหมากผู้หมากเมีย ศูนย์ถ่ายทอดเทคโนโลยีและสวนเกษตรผสมผสาน Utilization of Resources, Biodiversity and Local Wisdom for Tourism of Khung Bangkachao, Phrapradaeng District, Samutprakan Province The purposes of this research were 1) to promote utilization of products produced using resources, biodiversity and local wisdom in concave bank of Bangkachao and 2) to produce media for advertizing unique and distinctive products gained from community resources for promoting tourism in the target area. This research was a qualitative study. The data was collected from documents, survey, observation, interview, focus group discussion, and products selection by having cooperation with 36 community leaders, local scholars and relevant organization. Moreover, the signs of products described both in Thai and English were made and their pictures were shown on the signs in order that tourists will know the products value and are able to self-study the information. The research results revealed that the aforementioned area possessed interesting history, cultural ways, resources, biodiversity and diverse local wisdom. In addition, the products produced from these community assets were unique, distinctive and available in this area only. The following media for tourism were found: Mon Museum at Kanlad Temple, Cultural Hall at Bangkrasop Temple, and Ratrangson Temple, local wisdom of carving a banana stalk and making coconut-palm sugar, arts of paper cutting, nursery of yellow palms, center for technology transfer, and integrated agricultural garden.